Integrated Analysis of m6A Methylome in Cisplatin-Induced Acute Kidney Injury and Berberine Alleviation in Mouse - Shen, Jianxiao; Wang, Wanpeng; Shao, Xinghua; Wu, Jingkui; Li, Shu; Che, Xiajing; Ni, Zhaohui (Frontiers in Genetics, 2020)
Background：N6-methyladenosine (m6A) is the most abundant modification known on mRNAs. It participants in a variety of physiological and pathological processes, such as metabolism, inflammation and apoptosis. Aims: To explore the mechanism of m6A in cisplatin-induced acute kidney injury and berberine alleviation in mouse. Methods: This study investigated the N6-methyladenosine (m6A) methylome of kidneys from three mouse groups: C57 mice (controls), those with CI-AKI (injury group, IG), and those pretreated with berberine (treatment group, TG). Methylated RNA Immunoprecipitation NextGeneration Sequencing(MeRIP -seq) and RNA-seq were performed to identify the differences between the injury group and the control group (IvC) and between the treatment group and the injury group (TvI). Western blotting was performed to identify the protein levels of candidate genes. Results: In IvC, differentially methylated genes (DMGs) were enriched in metabolic processes and cell death. In TvI, DMGs were enriched in tissue development. Several genes involved in important pathways related to CI-AKI showed opposite methylation and expression trends in the IvC and TvI comparisons. Conclusion: m6A plays an important role in cisplatin induced acute kidney injury and berberine may alleviate this process.